#### Answer

y = -$\frac{9}{11}$

#### Work Step by Step

Solve: $\frac{1}{11}$ = y + $\frac{10}{11}$
$\frac{1}{11}$ = y + $\frac{10}{11}$
$\frac{1}{11}$ - $\frac{10}{11}$= y + $\frac{10}{11}$ - $\frac{10}{11}$
-$\frac{9}{11}$ = y

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

y = -$\frac{9}{11}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.